Tenant ShopeePay Fintech Application Acceptance Analysis Using TAM - Putri, Dhea Kesuma; Abdillah, Leon Andretti (Sinkron : jurnal dan penelitian teknik informatika, 2023)
This study aims to determine the analysis of tenant acceptance on the ShopeePay application in PTC using the Technology Acceptance Model. The type of data in this study is quantitative. Sample determination using a random sampling technique or purposive sampling obtained a sample of 56 tenants. Based on the results of the analysis using SPSS to find the influence between variables on information users, there is a relationship between perceived usefulness (X1) and image (X2) and tcount > ttable (5.889 > 1.997), there is a relationship between perceived usefulness (X1) and perceptions of usability (X8) and tcount > ttable (3.895 > 1.997), there is no relationship between image (X2) to perceptions of usability (X8) and tcount < ttable (1.871 < 1.997), there is a relationship between self-confidence (X3) to perceptions of ease of use (X7) and tcount > ttable (3.867 > 1.997), there is no relationship between anxiety (X4) to perceptions of ease of use (X7) and tcount > ttable (-1.041 < 1.997), there is a relationship between conditional facilitating (X5) and perceptions of ease of use (X7) and tcount > ttable (6.368 > 1.997), there is a relationship between perceptions of pleasure (X6) to perceptions of ease of use (X7) and tcount > ttable (10.825 > 1.997), there is a relationship between perceptions of ease of use (X7) to perceptions of usability (X8) and tcount > ttable (8.790 > 1.997).